Mandarin speech perception tests for Malaysian Chinese children - Cila Umat,; Chong, Sheue Lih; Siti Zamratol-Mai Sarah Mukari, (Penerbit UKM, 2010)
The study aimed to develop Mandarin speech perception tests for Malaysian Chinese children. Two tests were developed which were the Syllabic Pattern Perception Test (SPPT) and the Tone Perception Test (TPT). Both tests were designed for children aged between three to six years-old. A total of 80 normal hearing children aged 3 years to 6 years and 11 months from several kindergartens around Kuala Lumpur and Ipoh participated in this study. Results showed that the mean scores for the SPPT did not differ significantly across age (p > 0.05), possibly due to a ceiling effect. Although the SPPT showed relatively low test-retest and inter-rater Spearman correlation coefficients (r = 0.68 for correct syllable pattern response and r = 0.38 for correct item response), the scores were highly repeatable in both test-retest and interrater conditions. For the TPT, the mean scores of five and six year old children were significantly higher than three year old subjects while the mean score of four year old subjects was significantly poorer than the six years old. The test-retest and inter-rater reliability were high and the coefficients approximated 0.80 (p < 0.05). For both tests, gender and dialects or languages used as the second language did not have significant effect on the test scores. Content validity evidence was also collected from a group of panelists. In conclusion, SPPT and TPT are reliable and valid Mandarin speech tests to be used on Malaysian Chinese children who speak Mandarin.